Pengaruh Brand Image dan Inovasi Produk Terhadap Loyalitas Konsumen Smartphone Iphone : Studi Pada Mahasiswa di Kab. Sleman - Tasya Salsabilla; Jemadi Jemadi (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to analyze the influence of Brand Image and Product Innovation on Consumer Loyalty toward iPhone smartphones, with the research focused on university students in sleman regency. The increasing use of iPhones among students who are known to be critical and selective in choosing technology products forms the basis of this research. A quantitative approach was employed using a survey method, where questionnaires were distributed to 100 respondents who are iPhone users among university students in sleman regency. Data were analyzed using multiple linear regression with the assistance of SPSS version 26.